Kombinasi Fraksi Etil Asetat Jahe Merah (Zingiber officinale var. Rubrum) dan Jahe Emprit (Zingiber officinale var. Amarum) Sebagai Antioksidan - Hajrah Hajrah; Rolan Rusli; Yelfiani Li'lak Todingan (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2020)
Red ginger and emprit ginger are plants that are known to have flavonoid compounds with various benefits including antioxidants. This study aims to determine the total flavonoid levels of the ethyl acetate fraction of red ginger and emprit ginger and the IC50 value using the DPPH (2,2-Diphenyl-1-Picrylhydrazil) method. The highest level of total flavonoids in the ethyl acetate fraction in red ginger was 4,434 mgQE/g extract while in ginger emprit was 11,072 mgQE/g extract. The combination of the ethyl acetate fraction of red ginger and emprit ginger showed very strong antioxidant activity with an IC50 value of 19,027 ppm (1:1 combination), 17,649 ppm (1:2 combination), and 13,711 ppm (2:1 combination).